Development Of Waqf Based Microfinance And Its Impact In Alleviating The Poverty - Aulia Arifatu Diniyya (Universitas Ahmad Dahlan, 2019)
The purpose of this paper is to discuss the potential role of the institution of Waqf in poverty alleviation.Â Poverty is a complex, multi-dimensional phenomenon that has captured the attention of numerous scholars and agencies globally. The social role of the Islamic financial sector can be best exemplified by providing finance to the poor to increase their income and wealth. This paper will explore on how microfinance can be provided on Shariah compliant basis through Waqf model. This research also reviewing the development of the integrated Waqf based Islamic microfinance which aimed to provide solutions to reduce poverty. An integration of Waqf-based Islamic microfinance (IWIM) model is proposed to address all the practical challenges of microfinance faced in Muslim communities. In this model, microfinance is practised in compliance with Shariâ€™ah to address the multi-dimensional aspects of poverty and empowering the poor in order to enhance the socio-economic development and hence the well- being of the Ummah. With this aspiration, the IWIM model aims to tackle the challenges related to the scarcity of capital, inadequate human resources, absence of proper Takaful programs and project financing in an integrated approach. However, Waqf based microfinance still may be facing some problems should be addressed which related to credit risk, moral hazard, and economic viability.